STUDI KERAPATAN DAN KERAGAMAN LAMUN DI PANTAI BAMA TAMAN NASIONAL BALURAN - Selobing Purna Agung Indarto; Asri Sawiji; Dian Sari Maisaroh; Wiga Alif Violando (Universitas Muhammadiyah Gresik, 2021)
This research aims to find out the density and diversity of seagrass at Bama Beach, Baluran National Park, which was conducted in March 2019. In this study, seagrass was identified by quadrant transect method, with water quality measurement and association organisms were also measured. Three types of seagrass have been identified; Cymodocea rotundata, Enhalus acoroides, and Halodule universis. Among them, Cymodocea rotundata was found to be the most abundant seagrass species on Bama Beach with a density was up to 60%. The percentage of seagrass closure reached 35-56%. The water quality of the seagrass ecosystem showed optimal conditions for seagrass metabolism. Sea cucumber (Holothuria sp.) was found as an associated organism found in transects. In conclusion, the seagrass condition on Bama Beach showed high density and varied conditions.